Construction of education technology for the self-care of people with chronic kidney disease in hemodialysis (Research, Society and Development, 2022)
The study aimed to build an educational technology for self-care for people with Chronic Kidney Disease undergoing hemodialysis from the perspective of scientific production in the area. Therefore, a qualitative, descriptive and exploratory research was carried out through an Integrative Review. Subsequently, educational technology was built from a guiding instrument. Data collection took place in January 2021 and, after applying the inclusion and exclusion criteria, a total of twenty-one articles were obtained. The results pointed to six thematic categories most prevalent with regard to the main difficulties faced by this population regarding their self-care, however, the didactic material produced integrated all the themes identified, although they did not show expressiveness from a quantitative point of view. The educational technology, the product of this study, consists of a series of five booklets that are configured in serial, distinct and interdependent by-products. This work is perceived as relevant due to the theme studied being a public health problem in Brazil and worldwide, which impacts the quality of life of populations and requires health interventions aimed at promoting self-care. Furthermore, it is believed that the production of educational material contributes to the dissemination of health actions based on scientific evidence and, unlike other formats of academic productions, talks directly with the target audience, providing the general population with access to knowledge arising from research in the health area.